The Influence of Leadership and Motivation on Lecturer Performance - Dedi Mulyadi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This research was conducted to determine the effect leadership and motivation for the performance of lecturers at the faculty of Islamic religion at the University of Singaperbangsa Karawang, the object of research is all lecturers at the Faculty of Islamic Religion, Singapore University with a total of 34, the data collection technique uses a questionnaire. The results showed that the relationship between the independent variables, namely between X1 and X2, showed a correlation of 0.876, this shows that leadership and motivation at the Faculty of Islamic Religion, Singapore University have a strong relationship, meaning that leadership can encourage motivation. v Partial effect between leadership variables on performance amounting to 0.253. with the results of hypothesis testing, the level of significance is 0.012 <α (0.05), which means that there is a significant influence between leadership and performance. The partial effect of the motivation variable on performance is 0.737 with the results of testing the hypothesis with a significance level of 0.00 <α (0.05), which means that there is a significant influence between leadership and performance. The joint influence between leadership and motivation variables on performance is shown by the direct influence and indirect influence between leadership and performance by 22.7%, while between motivation and performance is 70.6%. So the overall leadership and motivation variables for performance are 93.3% ((RYX) 2). The joint influence between leadership and motivation variables on performance is shown by the direct influence and indirect influence between leadership and performance by 22.7%, while between motivation and performance is 70.6%. So the overall leadership and motivation variables for performance are 93.3% ((RYX) 2). The joint influence between leadership and motivation variables on performance is shown by the direct influence and indirect influence between leadership and performance by 22.7%, while between motivation and performance is 70.6%. So the overall leadership and motivation variables for performance are 93.3% ((RYX) 2).